Using ontology to build news network - M.S., Razali; A.Y., Yusufie; S.M.F.D., Syed Mustapha (2010)
One of the main activities in the knowledge sharing is to search and retrieve textual document.Traditional searching methods use user-specified keywords to search for documents.The common problem with this method is that the retrieved documents are not the ones that they are actually looking for even the searching is based on user-defined keywords The proposal in the research work is to build a well-defined domain where semantic relationship can be defined among the text documents in the repository to enhance the searching and retrieval performance.Reuters news is chosen as the domain where the ontology that defined the relationship is established to address the synonymy and polysemy problems.The ontology uses keywords to quantify the relationship strengths and labels the qualitative semantics.The ontology structure is a network of documents that is arranged based on hierarchy.This paper discusses the implementation of the document ontology which is applied to Reuters news corpus where the retrieval performance is measured based on the recall and precision.